2014
DOI: 10.1242/jeb.107987
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac responses to hypercapnia in larval zebrafish (Danio rerio): The links between CO2 chemoreception, catecholamines and carbonic anhydrase

Abstract: The ontogeny of carbon dioxide (CO 2 ) sensing in zebrafish (Danio rerio) has not been examined. In this study, CO 2 -mediated increases in heart rate were used to gauge the capacity of zebrafish larvae to sense CO 2 . CO 2 is thought to be detected via neuroepithelial cells (NECs), which are homologous to mammalian carotid body glomus cells. Larvae at 5 days post-fertilization (d.p.f.) exhibited tachycardia when exposed for 30 min to 0.75% CO 2 (~5.63 mmHg); at 7 d.p.f., tachycardia was elicited by 0.5% CO 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 64 publications
3
36
0
Order By: Relevance
“…Under hypoxic conditions, however, the HO/CO system has been shown to regulate cardiovascular function by modulating sympathetic tone in mammals (Hirakawa and Hayashida, 2006;Ding et al, 2008). In addition, it has been reported that the sympathetic nervous system is responsible for evoking the tachycardic response observed in larval zebrafish exposed to high environmental CO 2 (Miller et al, 2014) and therefore this may also be the mechanism responsible for the hypoxic tachycardia reported in this study. This notion was supported by the further increase of f H observed in hypoxic shamtreated larvae in the presence of adrenaline (from 155.0±5.7 to 187.0±5.7 beats min −1 ; data not shown).…”
Section: Presence Of Ho-1 In the Hearts Of Fishmentioning
confidence: 51%
“…Under hypoxic conditions, however, the HO/CO system has been shown to regulate cardiovascular function by modulating sympathetic tone in mammals (Hirakawa and Hayashida, 2006;Ding et al, 2008). In addition, it has been reported that the sympathetic nervous system is responsible for evoking the tachycardic response observed in larval zebrafish exposed to high environmental CO 2 (Miller et al, 2014) and therefore this may also be the mechanism responsible for the hypoxic tachycardia reported in this study. This notion was supported by the further increase of f H observed in hypoxic shamtreated larvae in the presence of adrenaline (from 155.0±5.7 to 187.0±5.7 beats min −1 ; data not shown).…”
Section: Presence Of Ho-1 In the Hearts Of Fishmentioning
confidence: 51%
“…Therefore, as this is the first time that sAC has been implicated in the control of heart rate, new roles for sAC in vertebrate hearts become a possibility. For example, hypercapnia produced tachycardia in embryonic zebrafish, a response blocked by atenolol, a β-adrenergic antagonist, and by a carbonic anhydrase inhibitor (Miller et al, 2014). Thus, it would be interesting to investigate whether KH7 might block this tachycardia, which would implicate a sAC-mediated control of heart rate in this case.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the ventilatory response was blunted in zebrafish chronically exposed to hypercapnia (Vulesevic et al, 2006), suggesting potential acclimation. And in zebrafish larvae, the tachycardia response to hypercapnia was absent in 7-day-old larval zebrafish (Miller et al, 2014), showing life-stage-specific differences. Thus, as reported in freshwater zebrafish, OA-relevant CO 2 disturbances could potentially affect CO 2 -sensing neurons in marine fish and trigger physiological responses, which could be compensatory or maladaptive.…”
Section: Co 2 -Sensing Peripheral Neuronsmentioning
confidence: 96%
“…Zebrafish neuroepithelial cells have been proposed to regulate important cardiorespiratory processes such as increasing ventilatory amplitude in adult zebrafish (Vulesevic et al, 2006) and tachycardia in 7-day-old larval zebrafish (Miller et al, 2014). Interestingly, the ventilatory response was blunted in zebrafish chronically exposed to hypercapnia (Vulesevic et al, 2006), suggesting potential acclimation.…”
Section: Co 2 -Sensing Peripheral Neuronsmentioning
confidence: 99%